Conversion of STOPP/START version 2 into coded algorithms for software implementation: A multidisciplinary consensus procedure - Huibers, Corlina J.A.; Sallevelt, Bastiaan T.G.M.; de Groot, Dominique A.; Boer, Maarten J.; van Campen, Jos P.C.M.; Davids, Cathelijn J.; Hugtenburg, Jacqueline G.; Vermeulen Windsant-Van den Tweel, Annemieke M.A.; van Hout, Hein P.J.; van Marum, Rob J.; Meulendijk, Michiel C. (International journal of medical informatics (Shannon, Ireland), 2019)
•Computerized screening tools support clinicians in reducing inappropriate prescribing.•STOPP/START criteria were converted into coded algorithms modeled as inference rules.•Multidisciplinary consensus facilitates universal interpretation of ambiguous criteria. The rapid digitalization of medical practice has attracted growing interest in developing software applications for clinical guidelines and explicit screening tools to detect potentially inappropriate prescribing, such as STOPP/START criteria. The aim of the current study was to develop and provide logically unambiguous algorithms of STOPP/START criteria version 2, encoded with international disease and medication classification codes, to facilitate the development of software applications for multiple purposes. A four round multidisciplinary consensus and validation procedure was conducted to develop implementable coded algorithms for software applications of STOPP/START criteria version 2, based on ICD, ICPC, LOINC and ATC classification databases. Consensus was reached for all 34 START criteria and 76 out of 80 STOPP criteria. The resulting 110 algorithms, modeled as inference rules in decision tables, are provided as supplementary data. This is the first study providing implementable algorithms for software applications based on STOPP/START version 2, validated in a computer decision support system. These algorithms could serve as a template for applying STOPP/START criteria version 2 to any software application, allowing for adaptations of the included ICD, ICPC and ATC codes and changing the cut-off levels for laboratory measurements to match local guidelines or clinical expertise.